Identifikasi Kesulitan Guru Melaksanakan Pembelajaran Daring Pada Siswa Kelas V SDN 33 Mataram Tahun Ajaran 2020/2021 - Liza Handayani; Karma, I Nyoman; Istiningsih, Siti (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
Online learning is an innovation in education so that learning objectives can still be achieved. However the teacher found it a little difficult because previously learning was done face-to-face (conventional). The application that is commonly used during online learning at the 33rd Mataram State Elementary School is the WhatsApp group platform. The purpose of this study was to identify the difficulties of fifth grade teachers during the use of WhatsApp groups, the effectiveness of WhatsApp groups during online learning, and the solutions of fifth grade teachers regarding difficulties during online learning. This research uses descriptive qualitative method. The data sources consist of fifth grade teachers A and fifth B with a sample selection technique in the form of purposive sampling. The data collection technique consists of observation, interviews, and documentation as well as data analysis using the Miles and Huberman model. The results showed that teacher difficulties consisted of unpreparedness with online learning, lack of student learning facilities, the WhatsApp application was the only one used, uneven distribution of quotas, obstruction distribution of learning resources, lack of apperception in learning, and lack of clarity in delivering learning materials. The use of WhatsApp groups is considered quite effective and the solution consists of teachers having to continue learning and participating in various trainings, providing quotas independently, group learning and maintaining good communication with student parents, distributing learning resources by online, material explanation with limited time and using varied media, suitability of the learning process with systematic lesson plans, and how to find out student understanding.